Impact of Chronic Risperidone Use on Behavior and Survival of 3xTg-AD Mice Model of Alzheimer’s Disease and Mice With Normal Aging - Torres-Lista, Virginia; López-Pousa, Secundí; Giménez-Llort, Lydia (Frontiers in Pharmacology, 2019)
Psychosis and/or aggression are common problems in dementia, and when severe or persistent, cause considerable patient distress and disability, caregiver stress and early institutionalization. In 2005, the FDA determined that atypical antipsychotics were associated with a significantly greater mortality risk compared to placebo which prompted the addition of an FDA black-box warning. The ACNP White Paper, 2008 reviewed this issue and made clinical and research recommendations regarding the use of antipsychotics in dementia patients with psychosis and/or agitation. Increased risk mortality has also being described in cerebrovascular adverse events in elderly users of antipsychotics. In the present work, at the translational level, we used male 3xTg-AD mice (PS1M146V, APPSwe, tauP301L) at advanced stages of the disease reported to have worse to survival than females, to study the behavioral effects of a low chronic dose of risperidone (0.1 mg/kg, s.c., 90 days, 13 to 16 months of age) and its impact on long-term survival, as compared to mice with normal aging. Animals were behaviorally assessed for cognitive and NPS (neuropsychiatric)-like symptoms in naturalistic and experimental conditions (open-field test, T-maze, social interaction, Morris water maze and marble test) before and after treatment. Weight, basal glucose levels and IPGTT were also recorded. Neophobia in the corner test was used for behavioral monitoring. Survival curves were recorded thought the experiment until natural death. The benefits of risperidone were limited, both at cognitive and BPSD-like level, and mostly restricted to burying, agitation/vibrating tail and other social behaviors. However, the work warns about a clear early mortality risk window during the treatment and long-lasting impact on survival. Reduced life-expectancy and life-span were observed in the 3xTg-AD mice, but total life-span (36 months) recorded in C57BL/6 × 129Sv counterparts with normal aging was also truncated, to 28 months in those with treatment. Sarcopenia at time of death was found in all groups, but was more severe in wildtype animals treated with risperidone. Therefore, the 3xTg-AD mice and their non-transgenic counterparts can be useful to delimitate critical time windows and for studying the physio-pathogenic factors and underlying causal events involved in this topic of considerable public health significance.